Inhibition of spring viraemia of carp virus replication in an Epithelioma papulosum cyprini cell line by RNAi. Issue 2 (27th January 2014) - Gotesman, M; Soliman, H; Besch, R; El‐Matbouli, M
Abstract Spring viraemia of carp virus (SVCV) is an aetiological agent of a serious disease affecting carp farms in Europe and is a member of the Rhabdoviridae family of viruses. The genome of SVCV codes for five proteins: nucleoprotein (N), phosphoprotein (P), matrix protein (M), glycoprotein (G) and RNA‐dependent RNA polymerase (L). RNA‐mediated interference (RNAi) by small interfering RNAs (siRNAs) is a powerful tool to inhibit gene transcription and is used to study genes important for viral replication. In previous studies regarding another member of Rhabdoviridae, siRNA inhibition of the rabies virus nucleoprotein gene provided in vitro and in vivo protection against rabies. In this study, synthetic siRNA molecules were designed to target SVCV‐N and SVCV‐P transcripts to inhibit SVCV replication and were tested in an epithelioma papulosum cyprini (EPC) cell line. Inhibition of gene transcription was measured by real‐time quantitative reverse‐transcription PCR (RT‐qPCR). The efficacy of using siRNA for inhibition of viral replication was analysed by RT‐qPCR measurement of a reporter gene (glycoprotein) expression and by virus endpoint titration. Inhibition of nucleoprotein and phosphoprotein gene expression by siRNA reduced SVCV replication. However, use of tandem siRNAs that target phosphoprotein and nucleoprotein worked best at reducing SVCV replication.